Studi Kelayakan Bisnis Produk “Toping Tahu Heboh (TOP Tahu) - Khairun Nisa, Seftya; Miradji, M. Affrizal; Stifani, Dwi Julia; Arditya Rangga , Muhammad Arya; Argitama, Jovian (Institut Nalanda, 2025)
This business feasibility study aims to evaluate the viability of the “Toping Tahu Heboh (TOP Tahu)” venture, an innovative stuffed tofu (tahu bakso) product enhanced with various toppings such as sausage, bird’s eye chili, and original/plain variants. The research employs comprehensive analysis covering market, technical, management, and financial aspects of a practical snack targeted primarily at students, young workers, and social-media-active Gen Z and millennial consumers. Market analysis reveals strong demand for innovative, convenient, and visually appealing affordable snacks. Technically, the production process is relatively simple, utilizing easily obtainable raw materials and controllable operational costs. The SWOT analysis highlights strengths in product uniqueness and competitive pricing, despite weaknesses in limited capital and threats from intense competition and raw material price fluctuations. Financial evaluation demonstrates attractive profit margins, with adjusted cost of goods sold per pack (3 pieces) and promising profitability potential as sales volume increases. Overall, based on all examined aspects, the “TOP Tahu” business is deemed feasible and possesses strong development prospects, particularly through enhanced by digital marketing optimization and continuous product innovation. This study also serves as practical application of entrepreneurship concepts for university students.